CONCEPT OF COLOR AND ITS PERCEPTION (Pedagogy of Higher and Secondary Education, 2022)
The to become, separate conformities to the law of color are examined, that have the large theoretical and practicalі value in the process of preparation of artist is a teacher.
Keywords: color tone; brightness; expressiveness